2021
DOI: 10.5851/kosfa.2020.e91
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Physicochemical and Sensory Quality Differences in Pork Belly and Shoulder Butt Cuts with Different Quality Grades

Abstract: Upload this completed form to website with submission ARTICLE INFORMATION Fill in information in each box below Article Title Investigation of physicochemical and sensory quality differences in pork belly and shoulder butt cuts with different quality grades

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…According to the Organization for Economic Cooperation and Development (OECD), in Korea, the annual pork consumption (31.6 kg per capita) was higher than that of beef (11.9 kg per capita) and poultry (18.8 kg per capita) ( OECD, 2021 ). Pork belly has been indicated as a strong preference among the various cuts of pork available in Korea ( Choe et al, 2015 ; Hoa et al, 2021 ). During distribution and storage of pork belly meat, quality can be decreased and various metabolites can be generated ( Triki et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the Organization for Economic Cooperation and Development (OECD), in Korea, the annual pork consumption (31.6 kg per capita) was higher than that of beef (11.9 kg per capita) and poultry (18.8 kg per capita) ( OECD, 2021 ). Pork belly has been indicated as a strong preference among the various cuts of pork available in Korea ( Choe et al, 2015 ; Hoa et al, 2021 ). During distribution and storage of pork belly meat, quality can be decreased and various metabolites can be generated ( Triki et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Narayan et al [ 52 ] reported that long chain n -3 FA possess health-promoting properties including EPA (C20:5 n -3) and DHA (C22:6 n -3), which were significantly higher in the SB-GLN-treated group meat compared to CON. Moreover, palmitic acid (C16:0) and stearic acid (C18:0) are considered to be predominant SFA in commercial pork meat [ 53 ]; such an FA profile was linearly increased in the SB-GLN-treated group pork belly fat, belly lean, and loin-lean meat. In 2012, Ross et al [ 54 ] reported that meat samples of pigs that were supplemented with probiotics showed higher PUFA contents with significantly higher ( p < 0.05) concentrations of linoleic acid (C18:2) and significantly lower monounsaturated FA; this partially agrees with the current findings.…”
Section: Discussionmentioning
confidence: 99%
“…Each the sample was prepared into sub-samples depending on the analysis. Due to the complicated structure with multiple muscles and intermuscular fat layers, the sampling manner was fixed for all the samples as shown in our previous study [ 22 ]. The physicochemical quality (proximate composition, pH, color, and cooking loss) was analyzed immediately after sampling (the day after slaughter), and the subsamples for fatty acid, volatile aroma and sensory evaluation were vacuum-packaged and stored at −20°C until use.…”
Section: Methodsmentioning
confidence: 99%